The influence of weather conditions on the Helsinki stock exchange - Marbehant, Arnaud (2020)
A connection between weather conditions and the mood of individuals has been established by numerous psychological studies. Moreover, mood seems to play a role in people’s decision-making processes and thus weather conditions may have an indirect influence on stock market returns. In our study based on regression analysis, we investigate the relationship between eight weather variables (precipitation, snow depth, average temperature, maximum temperature, minimum temperature, solar radiation, cloud cover and day length) and the returns of the OMX Helsinki Price Index from January 2000 to December 2019. In addition, we test whether the economic environment plays a role in the influence of weather on stock returns as investors might adapt their behavior depending on the prevailing economic conditions. Therefore, we break the 20-year period into four shorter time periods coinciding with the time before the subprime crisis, during the subprime crisis, after the subprime crisis and during the negative interest rate period. Furthermore, in addition to analyzing the absolute daily values of the weather variables, we also compare the daily values with an average of the preceding week based on the idea that for instance a sunny day is most likely to lift people’s mood after a week of bad weather. We find no conclusive answer as to whether the returns of the OMX Helsinki Price Index are influenced by changes in daily weather in Helsinki. Although our results show negative correlation between solar radiation and stock returns, we conclude that the reason for this is that stocks tend to go down in summer and thus there is no causal relation between high levels of sunshine and decreased returns. Our most promising findings are the negative correlation of precipitation and cloudiness and the positive correlation of snow depth. Even though we find some statistically significant correlation, the coefficients are extremely small, indicating that the possible economic impact of these weather variables on the OMX Helsinki index is very mild at best. In conclusion, our results do not confirm any significant impact of local weather on the Helsinki Stock Exchange, but they do not provide conclusive evidence in favor of the null hypothesis either. It is possible that improved methodology or different weather data would yield more conclusive results.